MODEL OF AN IMPROVED MULTI-LEVEL TRAINING SYSTEM FOR ENLISTED AND SERGEANT PERSONNEL OF THE NATIONAL GUARD OF UKRAINE - Buriak, Ihor (Honor and Law, 2025)
The article examines the problem of improving the training system for enlisted personnel and sergeants of the National Guard of Ukraine in the context of armed aggression and adaptation to international standards. Based on a comparative analysis of training models in NATO countries (the United States, Great Britain, Germany) and Ukraine, key differences are identified, in particular the lack of integration of leadership elements at the basic level. A model of improved multi-level training is proposed, which provides for the introduction of initial leadership courses at the stage of basic general training.